Integrating Ethics to Heart: Between Bureaucratization and Democratic Accountability on Government Auditor - I Gusti Ayu Purnamawati; Komang Fridagustina Adnantara (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This study analyzes the ethics and professionalism of government auditors of the Financial and Development Supervisory Agency of the Bali Provincial Representative Office. Research methods: The total sample of 65 people. This study employs a quantitative approach, utilizing a questionnaire with a 1-5 Likert scale for data collection. The analysis model uses Structural Equation Modeling. Findings: The study results indicate that professional ethics, education, and experience greatly influence the professionalism of government auditors. Suppose the government and institutions can implement measures to prevent fraud and budget irregularities early. In that case, clean, transparent, and accountable budget implementation principles can be implemented properly and comprehensively. Implication: Although public sector control has been largely overlooked in political theory, Aristotle, John Stuart Mill, and Max Weber emphasized the importance of the audit function to ensure that the power of public administration is not too broad, highlighting various aspects to shape its character. The Financial and Development Supervisory Agency will be effective if it carries out its functions and authorities properly and monitors and internally reports any deviations in budget implementation in the government and institutions.